INFLUENCE OF PRODUCT QUALITY ON CONSUMER PURCHASE INTEREST WITH CUSTOMER SATISFACTION AS A VARIABLE INTERVENING IN BLACK ONLINE STORE MARKET LHOKSUMAWE CITY: (Case Study on Black Market Online Store Customers in Lhoksumawe City) - Lasta Irawan, Ari; Multazam, Muhammad; Nur Ilham, Rico; Kayacilar, Cengiz (RADJA PUBLIKA, 2021)
This study aims to determine how the influence of product quality on consumer buying interest with customer satisfaction as an intervening variable in the Lhoksumawe City Black Market Online Store. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The data analysis method in this study uses simple linear regression analysis to obtain a comprehensive picture of the effect of product quality variables on consumer buying interest using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of hypothesis testing using simple regression analysis and t-test indicate that: the t-table value of the Product Quality variable is 7.644 > the t-table value (df: : 68%) is 1.995 so it can be concluded that product quality has a positive and significant effect on Consumer Buying Interest. Path analysis shows the direct effect of Product Quality X on Consumer Buying Interest Y of 0.670. Meanwhile, the indirect effect through Customer Satisfaction Z is 0.803 x 0.273 = 0.2192. From the calculation results obtained, it shows that the direct effect through Product Quality X is greater than the indirect effect on Consumer Buying Interest Y. 995 so that it can be concluded that product quality has a positive and significant effect on consumer buying interest. Path analysis shows the direct effect of Product Quality X on Consumer Buying Interest Y of 0.670. Meanwhile, the indirect effect through Customer Satisfaction Z is 0.803 x 0.273 = 0.2192. From the calculation results obtained, it shows that the direct effect through Product Quality X is greater than the indirect effect on Consumer Buying Interest Y. 995 so that it can be concluded that product quality has a positive and significant effect on consumer buying interest. Path analysis shows the direct effect of Product Quality X on Consumer Buying Interest Y of 0.670. Meanwhile, the indirect effect through Customer Satisfaction Z is 0.803 x 0.273 = 0.2192. From the calculation results obtained, it shows that the direct effect through Product Quality X is greater than the indirect effect on Consumer Buying Interest Y.